2016
DOI: 10.1158/0008-5472.can-15-2019
|View full text |Cite
|
Sign up to set email alerts
|

Forced Activation of Notch in Macrophages Represses Tumor Growth by Upregulating miR-125a and Disabling Tumor-Associated Macrophages

Abstract: Tumor-associated macrophages (TAM) contribute greatly to hallmarks of cancer. Notch blockade was shown to arrest TAM differentiation, but the precise role and underlying mechanisms require elucidation. In this study, we employed a transgenic mouse model in which the Notch1 intracellular domain (NIC) is activated conditionally to define the effects of active Notch1 signaling in macrophages. NIC overexpression had no effect on TAM differentiation, but it abrogated TAM function, leading to repressed growth of tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 50 publications
1
111
2
Order By: Relevance
“…In addition, this study also demonstrated that DAPT treatment could reduce the TAMs population in vivo . However, this phenomenon contradicts previous reports that TAMs with forced Notch activation exhibited an M1 phenotype and antitumour activity . It should be noted that Notch signaling could be activated to perform biological functions in cancer cells and tumour microenvironments.…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, this study also demonstrated that DAPT treatment could reduce the TAMs population in vivo . However, this phenomenon contradicts previous reports that TAMs with forced Notch activation exhibited an M1 phenotype and antitumour activity . It should be noted that Notch signaling could be activated to perform biological functions in cancer cells and tumour microenvironments.…”
Section: Discussioncontrasting
confidence: 86%
“…To further verify the regulation of miR-342-5p and Evl expression by Notch signaling in NS/PCs, we took advantage of NesCre transgenic mice and ROSA-Stop f -NICD mice (Zhao et al., 2016) to obtain NS/PCs with activated Notch signaling by culturing neurospheres from the E15.5 cortex and GE. By qRT-PCR, we found that the expression of Hes5 increased, whereas that of Hes1 increased in the GE but decreased in the cortex (Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…Normal C57BL/6 mice, Rbp-j -floxed ( Rbp-j f ) mice, ROSA26-Stop -floxed-NICD mice ( ROSA-Stop f -NICD), and Nestin-Cre ( NesCre ) mice were as described (Gao et al., 2009, Han et al., 2002, Zhao et al., 2016). NesCre mice were mated with Rbp-j f mice to obtain NesCre - Rbp-j f/f mice as cKO mice and NesCre - Rbp-j f/+ mice as controls.…”
Section: Methodsmentioning
confidence: 99%
“…RYBP target genes repress Wnt signaling [223] and others found that in undifferentiated myoblasts, TGFβ-Smad3 signaling enhances the recruitment of a complex, which contains YY1 and RYBP [241] confirming a possible tight functional link between RYBP and YY1. RYBP and YY1 also mediates the expression of miR-125a, which is a downstream mediator of Notch signaling [242], a signaling pathway important for epithelial-mesenchymal transition and numerous differentiation steps during lineage commitment of progenitor cells. Due to the early embryonic lethality of the Rybp homozygous null mice, the role of Rybp in later stages of embryonic development and lineage commitment was further studied in conditional gene ablations systems.…”
Section: Core Members Of Ncprcsmentioning
confidence: 99%
“…The latest studies found that YY1 interacts with SMAD7 and the interaction is attenuated by TGF-β signaling, and SMAD7 and YY1 together inhibit TGF-β-induced transcription in the nucleus [260]. RYBP and YY1 mediates the expression of miR-125a, which is a downstream mediator of Notch signaling [242] and YY1 is required for posttranscriptional stability of pluripotency factors, OCT4 and SOX2 [261].…”
Section: The Function Of Yy1mentioning
confidence: 99%